Fitoremediasi Tanaman Akar Wangi (Vetiver zizanioides) Terhadap Tanah Tercemar Logam Kadmium (Cd) Pada Lahan TPA Tamangapa Antang Makassar - Patandungan, Alfia; HS, Syamsidar; Aisyah, Aisyah Aisyah (Al-Kimia, 2016)
One example of soil contamination on land landfill is (TPA) Makassar. The method of prevention is phytoremediation of the contaminated land. This study examined the ability of the plant will vetiver (Vetiver zizanioides) in reducing the levels of Cd in the soil. To increase the potential of these plants to remediate Cd, the soil where the plants grow is combined with compost in which bacteria within the compost might improve the absorption of Cd. Planting medium used is pure soil and compost from Tamangapa Makassar. Research carried out for 28 days with a variation of the study. The composition of the media that the contaminated soil (TT) metal kadmium (Cd) and compost (K) with a ratio of 100% (TT): 0 K, 5 (TT): 1 (K), 4.5 (TT): 1.5 (K) and 4 (TT): 2 (K). The results shwed that vetiver plants were able to absorb Cd of 0,298 mg/Kg so it can be concluded that the composition of the planting medium with a combination of compost less significant because the combination of the contaminated soil with compost are less precise in helping vetiver plants accumulate or reduce metal pollution cadmium in contaminated soil Tamangapa Antang Makassar.